Epidemiological features of nontyphoidal Salmonella infections reported to foodborne disease surveillance system in china, 2013–2022 - Tongyu Wang; Weiwei Li; Ronghua Zhang; Jian Wen; Shuang Liu; Yuyan Jiang; Li Lin; Weiwei Chen; Jinjun Liang; Xiaochen Ma; Yijing Zhou; Haihong Han; et al. (BMC Public Health)
Abstract Background Nontyphoidal Salmonella (NTS) is the most commonly reported foodborne gastrointestinal infection and ranks among the top three causes of foodborne bacterial outbreaks in China. Methods This study analyzed NTS data from the Foodborne Disease Surveillance System in China from 2013 to 2022 to summarize epidemiological features and assess reporting rate changes. We employed joinpoint regression model to calculate the annual percentage change in NTS reporting rate, sex reporting rate, as well as rural-urban reporting rate. We applied the Pearson correlation coefficient to evaluate the correlation of NTS reporting rate and the national per capita consumption of major foods and cases of COVID-19. Results During this period, 55,266 NTS cases were reported, with reporting rates increasing significantly (AAPC [CRR] = 21.89%). Urban areas accounted for 70.06% of cases, but rural patients had higher hospitalization rates than urban ones (41.54% vs. 33.69%, p < 0.001). Children aged 0–4 years constituted 53.59% of cases and showed higher hospitalization rates (p < 0.05). Salmonella Typhimurium (31.07%) and Enteritidis (15.89%) were the leading serotypes. NTS reporting rates were strongly correlated with national per-capita consumption of fruit (r = 0.98), poultry (r = 0.95), aquatic products (r = 0.95), eggs (r = 0.94), vegetables (r = 0.79), dairy (r = 0.73), and meat (r = 0.65). Conclusion This study highlights the growing public health burden of Salmonella infection in China, with a sharp rise in reporting rates and major rural-urban differences. Over half of the cases involved children under 5 years old, underscoring the urgent need to enhance food safety measures, particularly for vulnerable populations.